We are what we pretend to be the first and last works - Vonnegut, Kurt 1922-2007 (Vanguard Press, 2012)
A posthumous double volume of the influential author's first and last written works, published to coincide with the 90th anniversary of his birth, includes the bitter satire "Basic training" and the unfinished final novel "If God were alive today"
Keywords: Massachusetts; College teachers / Fiction